Spatial and Temporal Trends in Contamination of the Czech Part of the Elbe River by Mercury Between 1991 and 2016 - Novotna, Kamila; Svobodova, Zdenka; Harustiakova, Danka; Mikula, Premysl (Bulletin of environmental contamination and toxicology, 2020)
We summarized available data concerning contamination of the Czech part of the Elbe River by mercury and assessed the potential risks to humans connected with the consumption of contaminated fish. Total mercury concentrations were evaluated in dorsal muscle of chub (Squalius cephalus) and bream (Abramis brama) that were collected at 11 sampling sites in the period from 1991 to 2016. Significant differences among sites were found for both species. The highest contamination was observed near the non-ferrous Kovohute metal works at Celakovice and also downstream from the Spolana chemical plant at Neratovice. A significant decline in contamination with time (concentrations decreasing from 1.65 to 0.22 mg kg-1; p = 0.004) was revealed in chub downstream from the Spolana plant. Calculated hazard indices (HIs) were below 1, therefore, adverse health effects on the general Czech population connected with the consumption of fish from the Elbe River were not expected.
Keywords: Mercury; Muscles; Humans; svaly; Heavy metals; Environmental Monitoring; Total mercury; řeky; časoprostorová analýza; lidé; zvířata; Rivers; monitorování životního prostředí; Pollution; rtuť; Spatio-Temporal Analysis; kontaminace potravin; Food Contamination; Czech Republic; Risk assessment; Water Pollutants, Chemical; Animals; Risk Assessment; Česká republika; hodnocení rizik; chemické látky znečišťující vodu; Cyprinidae